Risk assessment of cardiotoxicity to zebrafish (Danio rerio) by environmental exposure to triclosan and its derivatives. (October 2020) - Wang, Danting; Zhang, Yuhuan; Li, Jieyi; Dahlgren, Randy A.; Wang, Xuedong; Huang, Haishan; Wang, Huili
Abstract: Triclosan (TCS) and its two derivatives (2, 4-dichlorophenol and 2, 4, 6-trichlorophenol) are priority pollutants that coexist in aquatic environments. Joint exposure of TCS, 2, 4-dichlorophenol and 2, 4, 6-trichlorophenol, hereafter referred to as TCS-DT, contributes severe toxicity to aquatic organisms. There is currently a paucity of data regarding TCS-DT molecular toxicity, especially on cardiac diseases. We used zebrafish ( Danio rerio ) as a model organism, and evaluated the molecular-level cardiotoxicity induced by TCS-DT from embryonic to adult stages. TCS-DT exposure prominently led to phenotypic malformations, such as pericardial cysts, cardiac bleeding, increased SV-BA distance, decreased heart rate and reduced ejection fraction, as well as abnormal swimming behavior. Analyses of the GO and KEGG pathways revealed enrichment pathways related to cardiac development and screened for significantly down-regulated adrenaline signaling in cardiomyocytes. The cardiac marker genes ( amhc, cmlc2, vmhc, and nkx2.5 ) were obtained through protein-protein interaction (PPI) networks, and expressed as down-regulation by WISH. After chronic exposure to TCS-DT from 30 to 90-dpf, both body mass and heart indexes prominently increased, showing myocardial hypertrophy, abnormal heart rate and histopathological injury. Heart tissue damage included disordered and ruptured myocardial fibers, broken and dissolved myofilaments, nuclear pyknosis, mitochondrial injury and inflammatory cell infiltration. Further, abnormal changes in a series of cardiac functions-related biomarkers, including superoxide dismutase, triglyceride, lactate dehydrogenase and creatinine kinase MB, provided evidence for cardiac pathological responses. These results highlight the molecular mechanisms involving TCS-DT induced cardiac toxicity, and provide theoretical data to guide prevention and treatment of pollutant-induced cardiac diseases. Graphical abstract: Image 1 Highlights: Joint cardiac toxicity of TCS, 2, 4-DCP and 2, 4, 6-TCP to zebrafish is assessed. TCS-DT exposure causes a series of abnormal symptoms in zebrafish heart development. TCS-DT exposure decreases the expression of cardiac development marker genes. Joint exposure elevates the activities of cardiac biochemical marker enzymes. Down-regulation of adrenergic signaling pathways affects cardiac development. Abstract : Our study showed that zebrafish induced significant cardiac developmental toxicity after combined exposure to triclosan and its derivatives.